2019
DOI: 10.2106/jbjs.rvw.19.00031
|View full text |Cite
|
Sign up to set email alerts
|

Bone Cement in Total Hip and Knee Arthroplasty

Abstract: It is important to understand the mechanism of polymerization, mechanical properties, and environmental and temperature effects of polymethylmethacrylate.» The liquid component of bone cement comprises methylmethacrylate monomer, N,N-dimethyl-p-toluidine, hydroquinone, and possibly dye.» The powder component of bone cement contains benzoyl peroxide, beads of polymethylmethacrylate, possibly dye, zirconium dioxide or barium sulfate radiopacifier, and antibiotics. » Up to 2 g of powdered antibiotics added to a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Some biomaterials used to aid patients are bone cements. Their basic applications involve the mounting of hip and knee joint prostheses [ 5 ] and, in the area of spine surgeries, for vertebroplasty and kyphoplasty procedures [ 6 , 7 , 8 , 9 ]. The gold standard for today’s implant mounting procedures is the use of PMMA (poly methyl methacrylate) cements.…”
Section: Introductionmentioning
confidence: 99%
“…Some biomaterials used to aid patients are bone cements. Their basic applications involve the mounting of hip and knee joint prostheses [ 5 ] and, in the area of spine surgeries, for vertebroplasty and kyphoplasty procedures [ 6 , 7 , 8 , 9 ]. The gold standard for today’s implant mounting procedures is the use of PMMA (poly methyl methacrylate) cements.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated temperatures of 70° to 120°C, and in vivo studies have demonstrated temperatures of 40° to 50°C, with some reported data suggesting that in vivo temperatures can reach ≤70°C. 11 , 12 Although few studies have investigated the effect of thermal injury to vessel walls, Vo et al 13 described the dermal vascular changes that occur after thermal trauma. Such changes include thrombosis, vascular occlusion, necrosis, and rupture of blood vessels when exposed to temperatures of 50°C.…”
Section: Discussionmentioning
confidence: 99%
“…The manufacturer of Simplex P (Simplex brocher) Speedset cement recommends using 22.8 degree Celsius water bath for temperature equilibrium with powder, cement bowl, and mixing instruments right before mixing. The mixing [20] is performed for 1 min and the setting time is reproducible at 10 min. Other than using manufacturer's recommendation, one can devise their own standardized environment involving mixing instruments, cement bowl, the liquid and powder of bone cement, room temperature, humidity, etc.…”
Section: Discussionmentioning
confidence: 99%